Aeschylus Agamemnon 1035-41 - Davies, M (Firenze University Press, 2016)
Clytemnestra’s address to Cassandra at Aesch. Ag. 1035 ff. is shown to use much the same technique and ironic effect as Antilochus’ to Odysseus at Od. 21.293 ff. Both paradigms patronise the apparently helpless addressee, who is actually in a morally stronger position than the speaker.